The image of the hero in modern Ukrainian cinema. Interview with Anastasia Karpenko - Tymoshenko, Alyona (Ukrainian Cultural Studies, 2024)
Anastasia Karpenko is a popular Ukrainian film and theatre actress. She received the Best Actress award from the Ciné+ jury at the 75th International International Film Festival in Locarno for her role in the film How is Katya? ’, actress Kyiv Academic Theatre of Drama and Comedy on the left bank of the Dnipro River.